Interés general y Derecho Administrativo - Rodríguez-Arana Muñoz, Jaime (2023)
Public interest in a social and democratic state based on the rule of law is the key to understand the Administrative Law of today. Public interest is a specific concept, motivated, linked to the defense, protection and promotion of human dignity and the fundamental rights that come from and takes part in it.